2018
DOI: 10.4236/ojs.2018.86060
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of the Behrens-Fisher Problem under a Gamma Prior

Abstract: Yin [1] has developed a new Bayesian measure of evidence for testing a point null hypothesis which agrees with the frequentist p-value thereby, solving Lindley's paradox. Yin and Li [2] extended the methodology of Yin [1] to the case of the Behrens-Fisher problem by assigning Jeffreys' independent prior to the nuisance parameters. In this paper, we were able to show both analytically and through the results from simulation studies that the methodology of Yin [1] solves simultaneously, the Behrens-Fisher proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It can easily be seen that the posterior distributions of the difference of means derived by [6] and [7] under the different circumstances satisfy the conditions for Lemma 1 to hold. As such, Lemma 1 then proves mathematically that using either the Bayesian measure of evidence under Jeffreys' independent prior as obtained by [6] or under the Gamma prior as obtained by [7], both of which are extensions of the methodology of [5], will solve Lindley's paradox. Note that [6] did not provide a mathematical proof of the ability of the new Bayesian measure of evidence of [5]…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…It can easily be seen that the posterior distributions of the difference of means derived by [6] and [7] under the different circumstances satisfy the conditions for Lemma 1 to hold. As such, Lemma 1 then proves mathematically that using either the Bayesian measure of evidence under Jeffreys' independent prior as obtained by [6] or under the Gamma prior as obtained by [7], both of which are extensions of the methodology of [5], will solve Lindley's paradox. Note that [6] did not provide a mathematical proof of the ability of the new Bayesian measure of evidence of [5]…”
Section: Resultsmentioning
confidence: 88%
“…By the use of simulation results, this approach was shown to solve the two problems and also, it was shown mathematically to yield credible intervals that actually possess 1 − α coverage probability. [7] also extended the methodology of [5] by assigning Gamma priors to the precisions and showed mathematically that the paradox in [1] is avoided while solving the Behrens-Fisher problem. They also showed that results obtained by assigning Gamma priors to the precisions could coincide with results obtained by assigning Jeffrey's independent prior to the variances as is done in [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A prior distribution could be informative or non-informative, improper or conjugate. For a demonstration on the use of priors, see Nawaz and Aslam [8], Chandra and Rathavr [9], Aslam et al [10], Guure and Bosomprah [5], Yin [11], Yin and Zhao [12], Yin and Li [13], Goltong and Doguwa [14] and Goltong and Doguwa [15].…”
Section: Introductionmentioning
confidence: 99%